THE ROLE OF PARENTS IN COMMUNITY HOME SCHOOL A STUDY IN COMMUNITY HOME SCHOOL, SALATIGA (Universitas Negeri Semarang, 2015)
This descriptive qualitative study aims at determining the role of parents in home school community atthe Home School Community of Destiny Institute,Salatiga. The subjects of this study were 58 parents of home school community inDestiny Institute Salatiga. The technique of determining the subject used snowball sampling. Based on the results of data collection, itcan be concluded that the participation of parents in home schoolcommunity at Destiny Institute uses Curriculum Enrichment Model and Partnership or Shared Responsibilities Model. Parents of home school community in Destiny Institute are actively involved in learning activities, educational activities, and activities outside the studentâ€™s formal education. To measure the success of parental participation, indicators of successÂ are used, including 1) the parents and school conduct regular contact at least one semester; 2) the parents fully help their children at home, especially for parents who choose home school and parents should be able to mentor children's learning; 3) the parents volunteer to help school activities; 4) the parents as agents of society provide education and social services at schools for general public such as bazaar, outbound, and so on; 5) the parents are actively engaged toparticipate in decision-making in all sectors; and 6) the parents make choices for children on school type, program majors, and extracurricular activities.